Bryophytes of Atewa Forest, Eastern Region, Ghana. (2nd July 2016) - Hodgetts, N. G.; Essilfie, M. K.; Adu-Gyamfi, A.; Akom, E.; Kumadoh, J.; Opoku, J.
Abstract : Atewa Forest is a biodiverse tropical forest in the Eastern Region of Ghana, highly threatened by illegal mining, farming and hunting activities, and by proposals for industrial-scale bauxite mining. Conservation bodies are active in trying to save the forest and promote its future as a national park. Very little is known about its bryophyte flora, and this short expedition was intended as a first step to remedy that situation. Survey work in March 2014 was targeted mainly at areas thought likely to be bryophyte-rich, notably swamp forest and upland evergreen forest. A total of 164 species was recorded, including about 58 new to Ghana and at least one new species. The importance of Atewa Forest for biodiversity in western Africa is reinforced.